2008
DOI: 10.1007/s12032-008-9054-2
|View full text |Cite
|
Sign up to set email alerts
|

Serum neopterin levels in patients with breast cancer

Abstract: The aim of this study was to determine the importance of serum neopterin level in female patients with breast cancer of various clinical stages. The study consisted of 75 female patients with breast cancer who were diagnosed and treated at the Gazi University Department of Medical Oncology. The patients were classified into three representative groups and a control group: group A (n = 26), patients with newly diagnosed primary breast cancer and without metastasis; group B (n = 33), patients with metastatic bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 16 publications
(17 reference statements)
3
17
1
Order By: Relevance
“…In the present study serum neopterin levels were higher in DPR + patients and ANX + subjects, but they were not influenced by the diagnosis of breast cancer. This is in line with previous data sets showing that serum neopterin was not altered in patients with remitted breast cancer or local disease (Yildirim et al, 2008) possibly due to a cancer-induced suppression of the Th1-related immune response and lower IFN-␥ levels (Campbell et al, 2005). In breast cancer patients before therapy neopterin was increased in only 18% of the patients which is within the lowest frequency of all tumors (Murr et al, 1999).…”
Section: The Role Of Neopterin In Breast Cancer and Psychological Dissupporting
confidence: 89%
“…In the present study serum neopterin levels were higher in DPR + patients and ANX + subjects, but they were not influenced by the diagnosis of breast cancer. This is in line with previous data sets showing that serum neopterin was not altered in patients with remitted breast cancer or local disease (Yildirim et al, 2008) possibly due to a cancer-induced suppression of the Th1-related immune response and lower IFN-␥ levels (Campbell et al, 2005). In breast cancer patients before therapy neopterin was increased in only 18% of the patients which is within the lowest frequency of all tumors (Murr et al, 1999).…”
Section: The Role Of Neopterin In Breast Cancer and Psychological Dissupporting
confidence: 89%
“…Similarly, Yildrim et al [5] found that the serum levels of neopterin were higher in patients with metastatic breast cancer compared to patients without distal metastases. Unal et al [8] also observed that serum neopterin concentrations were significantly higher in patients with gastric carcinoma than in the control group and were correlated with tumor stage, gastric wall involvement and the number of metastatic lymph nodes.…”
Section: Discussionmentioning
confidence: 90%
“…We assessed the diagnostic utility of neopterin, which elevated serum and urinary levels were reported in breast, gastric and colon cancer [5,6,8]. We – as well as Birk et al [10] – observed elevated neopterin serum levels in patients with PA compared to the CP and healthy groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased neopterin concentrations have been reported across a range of disorders [3,18,19]. In cancer patients, systemic (serum or urinary) neopterin concentrations are increased across a range of different primary tumors [3,20,21], including breast cancer [22][23][24][25][26] or melanoma [20,21], and predict poor prognosis. Increased neopterin concentrations have been associated with the dysfunction of the immune system both in the tumor microenvironment [5,6] and at the systemic level [4,7].…”
Section: Discussionmentioning
confidence: 99%